The relationship between employee satisfaction and customer loyalty: The mediating role of customer experience - Pham, Duong Ngoc; Nguyen, Giang Thai (Edelweiss Applied Science and Technology, 2025)
This study examines the relationship between employee satisfaction (ESAT) and customer loyalty (CLOY) in traditional restaurants in Ho Chi Minh City, Vietnam. It specifically investigates the mediating roles of customer experience (CX) and employee loyalty (ELOY), contributing to the Service Profit Chain (SPC) framework and Herzberg’s Two-Factor Theory in the food and beverage (F&B) industry. Analyzing data from 306 matched employee-customer pairs using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results reveal that ESAT significantly enhances CX, which in turn strongly influences CLOY. However, ELOY does not mediate the ESAT-CLOY relationship. Additionally, motivators exert a greater influence on ESAT than hygiene factors, highlighting the critical role of intrinsic rewards in employee motivation. This study extends the SPC framework by confirming CX as a full mediator between ESAT and CLOY in traditional restaurants. It also reinforces Herzberg’s Two-Factor Theory by emphasizing the stronger impact of motivators over hygiene factors on ESAT, underscoring the importance of employee engagement in service quality improvement. Restaurant managers should focus on enhancing CX through employee engagement, training, and service quality improvements. Investing in employee motivation—particularly through recognition and career development—can significantly improve ESAT, leading to better CX and sustained customer loyalty.